Stress Drops of Intermediate‐Depth and Deep Earthquakes in the Tonga Slab - Tian, Dongdong; Wei, S. Shawn; Wang, Wei; Wang, Fan (Journal of geophysical research. Solid earth, 2022)
Multiple physical mechanisms have been proposed to explain the cause of intermediate‐depth and deep earthquakes, but they are still under debate. Source parameters such as stress drop, have the potential to provide insight into their physical mechanisms. We develop a modified spectral decomposition method to analyze 1‐year seismic data from temporary land‐based and ocean bottom seismographs in a complex subduction zone. By applying this method to investigate 1,083 intermediate‐depth and deep earthquakes in the Tonga slab, we successfully resolve the source spectra and stress drops of 743 MW 2.6–6.0 earthquakes. Although the absolute stress drops are subject to the choices of source model parameters, the relative stress drops are more reliably resolved. The median stress drop of Tonga earthquakes does not change with respect to magnitude but decreases with depth by 2–3 times in two separate depth ranges of 70–250 and 400–600 km, corresponding to intermediate‐depth and deep earthquakes, respectively. The median stress drops show spatial variations, with two high‐stress‐drop (five times higher than the ambient value) regions, coinciding with strong local deformation where the Tonga slab bends or tears. In the Tonga double seismic zone at 120–300 km depths, the median stress drop appears smaller in the lower plane than in the upper plane, suggesting a slower rupture velocity or a higher fluid content in the lower‐plane region. Our results suggest that intermediate‐depth and deep earthquakes in the Tonga slab generally follow the earthquake self‐similar model and favor the fluid‐related embrittlement hypothesis for both groups of earthquakes. Plain Language Summary Although earthquakes deeper than 70 km are observed in many subduction zones and sometimes cause damage to human societies, their nature is puzzling. This is because under high temperature and pressure conditions at great depths, rocks are expected to deform in a ductile way, like silly putty, rather than in a brittle way, like concrete. Multiple physical mechanisms have been proposed to explain these deep earthquakes, but they are still under debate. Stress drop, the change of shear stress after an earthquake, may provide insights into the physical mechanisms of these earthquakes. In this study, we estimate the stress drops of hundreds of deep earthquakes beneath the Tonga Trench where the Pacific plate subducts underneath the Australian plate. We find that stress drops of these earthquakes do not change with respect to earthquake magnitudes but show depth‐dependence in two separate depth ranges (70–250 and 400–600 km). We also find abnormally high stress drops in two regions where the subducted Tonga slab undergoes strong deformation. At 120–300 km depths, earthquakes occur along with two separate parallel layers. The lower‐plane earthquakes have smaller stress drops than the ones in the upper plane, possibly implying water carried to great depths by subduction. Key Points Earthquake stress drops show no magnitude dependence and slight depth dependence High stress‐drop zones coincide with dramatic changes in the Tonga slab geometry In the Tonga double seismic zone at 120–300 km, the lower‐plane earthquakes have smaller stress drops than the upper‐plane earthquakes